Conjugated heat and mass transfer in convective drying in compact wood kilns: A system approach - Vaz Jr. M.* (2013)
Drying is a required operation in timber manufacturing industries. Most drying processes utilise convective kilns, which involve coupling between transient heat and mass (moisture content) transfer in solids and convection in a flowing medium. In the present work, the flow field in the kiln is determined using a system approach based on a general head loss equation, whereas the coupling between transient heat and mass transfer in the timber is accomplished by a solution of a local differential model across the timber stack. The scheme is applied to study the effects of distinct geometric kiln configurations and air flow temperatures upon drying rates and moisture content. © 2013 M. Vaz Jr. et al.